The influence of malocclusion on social aspects in adults: study via eye tracking technology and questionnaire - Gil Guilherme Gasparello; Sergio Luiz Mota Júnior; Giovani Ceron Hartmann; Thiago Martins Meira; Elisa Souza Camargo; Matheus Melo Pithon; Orlando Tanaka (SpringerOpen, 2022)
Abstract Background Smile esthetics has a strong influence on perception, attractiveness, and personal characteristics. It is unknown how malocclusions may influence the appearance of the individual's smile. This study aimed to investigate whether malocclusion affects the visual perception of esthetics, age, employability, honesty, intelligence and to meet its obligation in time in middle-aged adults. Facial frontal smiling photographs of a male and a female middle-aged adult with 3 different malocclusions were shown to and evaluated by 90 laypeople (non-dentists), divided into groups: young adults (14-44 years), middle-aged adults (45-59 years), and elders (over 60 years). The index of treatment need (IOTN) was used, and IOTN 1, 5, and 8 images were created in Photoshop using the male and female photographs. In total, 6 photographs were evaluated, 3 areas of interest (AOI)-eyes, nose, and mouth-were created for statistical comparison. The Ogama and Eye Tribe tracker were used in conjunction to measure eye tracking. A visual analog scale (VAS) was employed with a questionnaire surveying individuals' perception of age, employability, honesty, intelligence, and ability to meet obligations. Kruskal-Wallis, one-way analysis of variance, Pearson's-chi-squared, and Pearson correlation test were applied. Results No statistical difference was found in complete fixation time and time until the first fixation for each AOI for eye-tracking. VAS showed statistical differences in the male and female IOTN 1 images when compared with the IOTN 5 and 8 for both models, and there was no difference between genders in the IOTN 1. As the perceived age of the model increased, the chances of getting hired decreased. Employability, honesty, intelligence, and ability to meet obligations showed higher values for IOTN 1. There were significant differences between age ranges; perception of intelligence in the female IOTN 1 model (p = 0.002) and IOTN 8 model (p < 0.001) and honesty between young adults and middle-aged adults in the male IOTN 1 and 8 images (p < 0.001). Conclusions There was a difference between age groups in the perception of honesty and intelligence. A well-balanced and attractive was perceived as more youthful and attractive in both genders and may increase the chance of being selected for a job interview or being hired.